Morphological and molecular identifications of ectoparasites infesting the gills of scalloped spiny lobster Panulirus homarus Linnaeus, 1758 - KISMIYATI KISMIYATI; YUSUF TAUFIK HIDAYAT; MUHAMAD AMIN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kismiyati, Hidayat YT, Amin M. 2024. Morphological and molecular identifications of ectoparasites infesting the gills of scalloped spiny lobster Panulirus homarus Linnaeus, 1758. Biodiversitas 25: 372-378. Ectoparasite infestation has been reported to cause stress, weaken the immune system, and disturb respiratory systems, which lead to death in cultured spiny lobsters. Many lobster farmers have reported an infestation of ectoparasites in cultured scalloped spiny lobsters in West Nusa Tenggara, Indonesia. However, fewer studies have been conducted to identify the ectoparasite-infesting scalloped spiny lobster cultured in West-Nusa Tenggara Province. Thus, using morphological and molecular approaches, the present study aimed to identify ectoparasites infesting scalloped spiny lobsters (Panulirus homarus Linnaeus, 1758). A total of 30 scalloped spiny lobsters were collected from lobster farmers at Ekas, East Lombok, West Nusa Tenggara, Indonesia, and ectoparasites were observed and identified morphologically under a microscope as well as confirmed using CO1 gene sequences. The results showed that the ectoparasites were morphologically identified as Octolasmis angulata Aurivillius, 1894 and Octolasmis lowei Darwin, 1852. Similarly, based on the mtDNA sequence of the COI region (~721 bp length), the ectoparasite was also referred to O. angulata (95.65% similarity) and Octolasmis lowei (~683 bp length) with a similarity of 98.75%. These results suggest that ectoparasite has become one potential disturbance in lobster aquaculture; therefore, preventing or curing strategies should be developed.